If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x * x + -6x + 5 = 0 Multiply x * x x2 + -6x + 5 = 0 Reorder the terms: 5 + -6x + x2 = 0 Solving 5 + -6x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (1 + -1x)(5 + -1x) = 0Subproblem 1
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Subproblem 2
Set the factor '(5 + -1x)' equal to zero and attempt to solve: Simplifying 5 + -1x = 0 Solving 5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5Solution
x = {1, 5}
| 1w-6=-8 | | .333w-6=-8 | | 4x-5=12x-56 | | X-6x+5= | | 3x*4y=4 | | 3x=2,1 | | 1/3+1=9 | | 1/3=8 | | 4(x-5)+x=5(x-5)+5 | | 46=2(3-2x) | | 3p+24q+42= | | 13(x-2)-2x=7 | | 191-2x=34x+23 | | 5n-2=n+5 | | 8x-4x+2x-6x= | | -6x=2y+12 | | 4x^2+33x=-54 | | 8x-4x+(4x-8)/2-4x/3-6x+4=x+2-16 | | -log(x)=1.5 | | 4(x-9)=4 | | 85-3X=10+20 | | x=5.33 | | (2x^2)-11x+12=0 | | 2X-2=9X-29 | | (x+4)(x+6)+8=x(x+1)-13 | | 17x^2-46x+14=81 | | 0=3k^2+2k-40 | | (-3x+1)-(-3x+1)+12x=-3 | | (-3x+1)-(-3x+1)=+12x | | 3x+8=5x-6(x-4) | | 4x-x+5=20 | | (-3x+1)=-(-3x+1)+12x |